David E. Ramsett. Regional Industrial Development in Central America : A Case Study of the Integration Industries Scheme. Nueva York : Frederick A. Praeger, 1969. xvi, 133 p. - Urquidi, Víctor L. (Estudios Demográficos y Urbanos, 1970)
DAVID E. RAMSETT, Regional Industrial Development in Central America: A Case Study of the Integration Industries Scheme. Nueva York, Frederick A. Praeger, 1969.